Politik, Ökonomie und Lebensstil in dem globalen Kapitalismus. Eine Überlegung auf der Grundlage von Georg Simmel - Mele, Vincenzo (Simmel Studies, 2016)
Georg Simmel’s paradoxical concept of Lifestyle opens up an extensive field of issues and a wide perspective on individual existence in contemporary society. On one side it makes possible to understand several aspects of the “aesthetisation of everydaylife” that characterize the current global consumer culture. On the other side help us to focus on different aspects of individual participation in the political and social life of the community and entails many nuances that are not immediately accessible from the point of view of the classical concept of citizenship. Such a richer interpretive perspective becomes viable if the concept of lifestyle is understood in the Simmelian meaning of the Individual Law: an ethical principle that makes sense of a plurality of sphere of activities otherwise severed – as the rationalized modern life imposes upon individuals.